THE CONSTRUCTION OF FEMALE GENITAL MUTILATION IN TEMBELING TANJUNG, RIAU ARCHIPELAGO PROVINCE - Marisa Elsera; Neverandle Kadingga Wardhana; Sri Wahyuni (BUANA GENDER : Jurnal Studi Gender dan Anak, 2023)
In the social process, individual humans are seen as relatively free creators of social reality in their social world, therefore the construction built by each individual is different, until the emergence of a phenomenon, namely the construction of female circumcision. Reality is the result of creative human creation through the power of social construction of the social world around them. Female Genital Mutilation (FGM) is a hereditary custom that has become a tradition. This research was conducted to find out the construction of the tradition of circumcision in girls. The informants in this study were nine, namely the people of Tembeling Tanjung who did and did not circumcise girls and community leaders. This type of research is qualitative and the selection of informants uses purposive sampling technique with several predetermined criteria. From the results of the research, there were various kinds of social constructions in the tradition of Female Genital Mutilation (FGM) in Tembeling Tanjung. This dialectical process occurs through externalization, objectivation, and internalization. In externalization, it is known that informants adapt values and norms in the form of adjustments in the implementation of circumcision. Informants' internalization of values and norms in socialization with family, religious leaders, community leaders and the social environment gave birth to an understanding of the objectivation of female circumcision. This is what causes informants to continue to actualize the tradition of Female Genital Mutilation (FGM).